Galfa-i2 signaling is required for skeletal muscle growth, regeneration, and satellite cell proliferation and differentiation. - Minetti, Giulia C. (2014)
We have previously shown that activation of G i2, an subunit of the heterotrimeric G protein complex, induces skeletal mus-cle hypertrophy and myoblast differentiation. To determine whether G i2 is required for skeletal muscle growth or regenera-tion, G i2-null mice were analyzed. G i2 knockout mice display decreased lean body mass, reduced muscle size, and impairedskeletal muscle regeneration after cardiotoxin-induced injury. Short hairpin RNA (shRNA)-mediated knockdown of G i2 insatellite cells (SCs) leads to defective satellite cell proliferation, fusion, and differentiationex vivo. The impaired differentiationis consistent with the observation that the myogenic regulatory factors MyoD and Myf5 are downregulated upon knockdown ofG i2. Interestingly, the expression of microRNA 1 (miR-1), miR-27b, and miR-206, three microRNAs that have been shown toregulate SC proliferation and differentiation, is increased by a constitutively active mutant of G i2 [G i2(Q205L)] and counter-regulated by G i2 knockdown. As for the mechanism, this study demonstrates that G i2(Q205L) regulates satellite cell differen-tiation into myotubes in a protein kinase C (PKC)- and histone deacetylase (HDAC)-dependent manner.